Textisms as a Non-sexist Language Mechanism. Digital Communication and Educational Effects - Núñez-Román, Francisco; Hunt-Gómez, Coral Ivy; Gómez-Camacho, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Twitter has been used as a platform for feminist movements such as #MeeToo and promotes the use of inclusive language through a specific type of textisms that use -@ and -x as gender-inclusive marks. This paper studies the use that teachers working with adolescents make of these marks in virtual educational communities on Twitter through public data mining and text analysis. The results show a high use of -@ and -x among teachers in their interactions, which makes them models for the adoption of innovative linguistic mechanisms favoring gender equality that can be subsequently adopted by adolescents’ digital communications.